Third Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 12-17, 1989. Day 5. Plenary session. Tape 3 of 4 - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1989)
A mock trial is conducted to present the complex issues involved in integrating exceptional children (in this case a child with down syndrome) in the school system and give some insight as to what is to be expected in the national scene on this topic. The trial is based on the sections of the Charter of Rights and Freedoms ss. 15, 2(d) and s. 24(1) concerning equal access to education. Participants include Lloyd Wicks, Jim Walsh, Randell Earle, Ron Wiggins, Linda Wiggins, Gilbert Thomas, Anne Power, Diana McKinnon, Frank Lee, Shirley Cole, Glen Sheppard, and Kathleen Taylor. Does not take up from end of tape 2